2019
DOI: 10.1016/j.jallcom.2019.05.347
|View full text |Cite
|
Sign up to set email alerts
|

The role of samarium incorporated structural defects in ZnO thin films prepared by femtosecond pulsed laser deposition

Abstract: Samarium, a rare-earth element is used as an impurity in ZnO to study the effects it causes in structure thereby changing the optical and electrical characteristics of ZnO thin films. Samarium zinc oxide (SmxZn1-xO, SZO) films are deposited on glass substrates employing femtosecond pulsed laser deposition (fs-PLD). XRD results show that all films are crystalline and prefer c-axis growth. 1 wt.% Sm is plausible for doping in ZnO and 2 wt.% samarium addition results in reaction among impurity and host atoms form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The results were not clearly reported, but they seemed to indicate that crystalline ZnO films were deposited. This was different to the approach of Hashmi et al, who studied the role of a dopant in the growth of ZnO films [63]. The laser source was the same as already used by the same group [61], while the dopant was samarium.…”
Section: Zinc Oxidementioning
confidence: 96%
“…The results were not clearly reported, but they seemed to indicate that crystalline ZnO films were deposited. This was different to the approach of Hashmi et al, who studied the role of a dopant in the growth of ZnO films [63]. The laser source was the same as already used by the same group [61], while the dopant was samarium.…”
Section: Zinc Oxidementioning
confidence: 96%
“…Luo et al (2019) synthesized a novel samarium complex that emits red light and has potential as a red light emitting material for LEDs. Meanwhile Hashmi et al (2019) studied the effects of samarium incorporation in ZnO thin films and found that it affected the optical and electrical characteristics of the films, making them suitable for use in optical devices for UV and blue emission. Marzouk and Hammad (2020) found that samarium oxide affects the structural and optical properties of bismuth glass, making it suitable for photonic applications.…”
Section: Introductionmentioning
confidence: 99%
“…There are various deposition methods to fabricate ZnO based films, including hydrothermal synthesis [22], spray pyrolysis [23], chemical vapor deposition [24], magnetron sputtering [25], pulsed laser deposition [26] and electrodeposition [27]. Among these, the sol-gel technology is advantageous due to its low operation cost, non-vacuum requirements, non-expensive equipment, large area film deposition, compositional modifications, precise microstructural and chemical control, reproducibility and the possibility of engineering the film properties.…”
Section: Introductionmentioning
confidence: 99%